Turkish-Russian relations in the era of President Erdogan - Mohamed Saleem, . Assistant Professor Dr. Nabil (The college of law and political science journal, 2023)
The history of raelation between ottoman Turkey and Tsardom of Russian wasDJJUHVVLYHLQJHQHUDOIRUDSSUR[LPDWHO\ÀYHFHQWXULHVEHFDXVHRIJHRSROLWLFDOcompetition and struggle , rather economical , religious , cultural motives.The geopolitical reasons continued to be raised as a causes for differencesbetween the two countries , and above international coalitions especially afterworld war two.%\WKHUHDFKRI´MXVWLFHDQG'HYHORSPHQWµSDUW\WRSRZHULQ7XUNH\DQGWKHpresence of Vladimir potin on the head of power in Russia , the ralations betweenthem developed remarkably despite the regional and international challenges.What is the feature of this relations , is what the research trying to outlook.